HA-MOP knockin mice express the canonical µ-opioid receptor but lack detectable splice variants - Sebastian Fritzwanker (Nature Portfolio, 2021)
Fritzwanker et al. develop a knock-in transgenic mouse line in which the hemagglutinin epitope tag sequence is fused with the amino-terminus of the µ-opioid receptor. Their model enables more efficient immunodetection of G protein-coupled receptors.